2018
DOI: 10.1002/aenm.201801120
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Electrolytes Design for Capacity‐Equivalent Dual‐Graphite Battery with Superior Long‐Term Cycle Life

Abstract: Based on cation/anion graphite intercalation chemistry (GIC) processes, dual‐graphite batteries promise to be an energy storage device of high safety and low cost. However, few single electrolyte systems can simultaneously meet the requirements of both high oxidative stability during high voltage anion‐GIC on cathode and high reversibility upon cation‐GIC on anode. Thus, in order to rigidly remedy the irreversible capacity loss, excessive electrode materials need to be fabricated within full cell, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 49 publications
(157 reference statements)
0
33
0
Order By: Relevance
“…The DCB can be charged to 4.5 V and delivered a specific capacity of 68 mAh g −1 based on the total mass of electrodes at a specific current of 50 mA g −1 . In an attempt to take full advantage of ether‐based electrolytes, an innovative dual‐organic electrolyte (IL–ether hybrid electrolyte) has been designed for dual‐graphite batteries by Qiao et al . The LiTFSI–triethylene glycol dimethyl ether (1 : 1 molar ratio) electrolyte on the anode ensures a high reversibility of Li + de‐/intercalation, while the 1.5 M LiTFSI–Pyr 13 TFSI electrolyte within the cathodic side can endure high potentials.…”
Section: Conventional Liquid Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The DCB can be charged to 4.5 V and delivered a specific capacity of 68 mAh g −1 based on the total mass of electrodes at a specific current of 50 mA g −1 . In an attempt to take full advantage of ether‐based electrolytes, an innovative dual‐organic electrolyte (IL–ether hybrid electrolyte) has been designed for dual‐graphite batteries by Qiao et al . The LiTFSI–triethylene glycol dimethyl ether (1 : 1 molar ratio) electrolyte on the anode ensures a high reversibility of Li + de‐/intercalation, while the 1.5 M LiTFSI–Pyr 13 TFSI electrolyte within the cathodic side can endure high potentials.…”
Section: Conventional Liquid Electrolytesmentioning
confidence: 99%
“…b) Charge/discharge curves and c) cycling performance at 100 mA g À 1 of the DCB fabricated by the hybrid electrolyte. Reproduced with permission from Ref [112]…”
mentioning
confidence: 99%
“…proposed a hybrid electrolyte strategy for dual‐graphite battery. [ 12 ] The anion intercalation into graphite positive electrode in ionic‐liquid catholyte contributed a high working potential. Xu and co‐workers developed a localized high‐concentration electrolyte composing of triethyl phosphate, ethylene carbonate, and a partially fluorinated ether, which exhibited benign compatibility with graphite anode and high‐voltage transitional metal oxide cathodes.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that successful uses of hybrid electrolytes for lithium ion batteries have enabled the energy storage system to reach higher operating voltages. For example, an ionic liquid at the cathode and a super concentrated ether based electrolyte at the anode, are separated by one layer of Nafion membrane with intercalated electrodes and can reach a high voltage of 4.2 V. [46] Similarly, coupling Li/Pyr 13 TFSI to equimolar LiTFSI/G3 complex and utilizing LiNi 0.5 Mn 1.5 O 4 /graphite cathode can deliver an operating voltage of 4.7 V, with an excellent capacity retention. [47] This research has demonstrated that in principle all quinone flow batteries can be modified to accommodate an alkaline solution in the anode side and an acidic solution in the cathode side, using a single cation-exchange membrane to maximize the benefit gained from pH-dependent redox potential of the quinone compounds that rely on deprotonation.…”
Section: Introductionmentioning
confidence: 99%